39PExploring the role of the DDB2 protein as a potent molecular target in pancreatic ductal adenocarcinoma. (7th November 2019) - Gilson, P; Meras, M; Ariztegui, M; Becuwe, P; Merlin, J-L; Harlé, A
Abstract: Background: Pancreatic ductal adenocarcinoma (PDAC) has a poor prognosis with a 5-year survival rate of 6%, emphasizing the need for new therapeutic targets and prognostic biomarkers. The damage-specific DNA-binding protein 2 (DDB2) is involved in damaged-DNA repair through the Nucleotide Excision Repair system and has been recently demonstrated as playing a role in mammary, ovarian and colorectal carcinogenesis by stimulating tumour growth, inhibiting migration and invasion and sensitizing tumour cells to chemotherapy. The potent role of DDB2 on pancreatic cancer development has not been explored yet. Given the induction of TGF-β signalling pathway by DDB2 and the TGF-β pathway activation in 47% of PDAC according to the TCGA, we aim to evaluate the role of DDB2 in PDAC. Methods: DDB2 expression level was determined in 3 PDAC cell-lines (T3M4, BxPC3, Capan-2) by Western blot and RT-PCR. Knock-out and knockdown DDB2 models were established from DDB2-overexpressing cells (using CRISPR-Cas9 technology and ShRNAs respectively) to evaluate the role of DDB2 protein in cancer cell proliferation, differentiation potential, migration and invasion. Results: Overexpression of DDB2 was found in T3M4 and BxPC3 cells and under expression in Capan-2 cells (p < 0.001). T3M4 knock-out and knockdown-DDB2 cells, that exhibited a DDB2 silencing of 99% and 90% respectively, had a doubling time significantly higher than T3M4 transfection control and non-transfected cells (p < 0.05). No substantial morphologic change was noticed in DDB2-deficient cells, however preliminary results reported migration and invasion improved in DDB2 deficient cells as well as a modification in the expression of epithelial-mesenchymal transition factors (N-cadherin, E-cadherin and cytokeratin 19). Conclusions: These preliminary results show the potent role of DDB2 in PDAC cells proliferation and the regulation of epithelial-mesenchymal transition, cell motility and invasiveness. The next steps of our work will be to explore DDB2 regulation mechanisms to understand whether its expression may be modified using targeted therapies and to elucidate its role as a prognosis marker in fresh frozen samples of patients with PDAC. Legal entity responsible for the study: Université de Lorraine, CNRS UMR 7039 CRAN, Institut de Cancérologie de Lorraine. Funding: «Action Incitative du CRAN» funded by the CNRS UMR 7039 CRAN. Disclosure: All authors have declared no conflicts of interest.